Pertussis Toxin Ameliorates Microglial Activation Associated With Ischemic Stroke - Zhou, Feihui; Liu, Rong; Han, Pengcheng; Zhang, Xingkui; Li, Zhigao; Zhang, Shen; Liu, Chang; Xia, Yang; Tang, Zhiwei (Frontiers in Cellular Neuroscience, 2020)
Objective: To investigate the effect and the underlying mechanism of pertussis toxin on microglia in the setting of cerebral ischemia. Method: We tested the effect of pertussis toxin 400ng/don MACO stroke model by evaluating the neurologic function, infarct size, microglial distribution and activation. In parallel, we also tested the effect of pertussis toxin on primary cultured microglia by evaluating microglial proliferation, activation, cytokine release and CX3CR1 expression. Results: Pertussis toxin reduced the post-stroke infarct size, improved the neurologic function as evaluated by Longa score, and reduced microglial aggregation and activation in the infarcted area. Further, pertussis toxin significantly decreased LPS-stimulated microglial proliferation, the release of Interleukin-1β and Tumor Necrosis Factor-α, and the expression of CX3CR1. Interpretation: Pertussis toxin treatment in stroke reduced microglial accumulation and activation in the infarct zone, resulting in a better functional outcome. The benefits of pertussis toxin treatment may be attributed to the reduced production of pro-inflammatory cytokine such as IL-1β and TNF-α, and reduced expression of chemokine CX3CR1.